Epidemiologic and Outcome Analysis of Epistaxis in a Tertiary Care Center Emergency Department. Issue 1 (January 2020) - Bui, Roger; Doan, Nicolette; Chaaban, Mohamad R.
Background: The association between hypertension and recurrent epistaxis is controversial. The objective of this study is to examine the factors associated with recurrent epistaxis visits to the emergency department (ED) and establish an otolaryngology (ENT [ear, nose, and throat]) consult algorithm to optimize treatment and minimize unnecessary consultation. Methods: A retrospective review of 100 patients presenting to the ED for epistaxis requiring ENT consult from 2013 to 2018 was conducted. Patient demographics, comorbidities, epistaxis etiology, blood pressure measurements during admission, and treatment methods were analyzed. Patient charts were reviewed for ED admissions, complications, and procedures. A consult algorithm was subsequently devised and retrospectively applied to our cohort. Results: Patients who required more than one ED visit for epistaxis were more often males (77.8% vs 49.3%, P  = .01), required posterior packing (51.9% vs17 .8%, P  < .001), and had more comorbid hypertension (66.7% vs 38.4%, P  = .01) compared to patients who had 1 visit. Compared to patients presenting during summer and fall (May–October), patients presenting during winter and spring (November–April) were more often treated for anterior epistaxis with Surgicel®/Surgifoam® rather than posterior nasal packing (57.4% vs 37.0%, P  = .04). Application of our consult algorithm decreased consultation by 78% and liberated 58.5 hours of ENT resident time. Conclusion: Patients with recurrent epistaxis tended to be male and had more comorbid hypertension. Further prospective studies are warranted to ascertain the factors associated with recurrent epistaxis. Our consult algorithm for epistaxis helped reduce unnecessary ENT consultation and facilitated reallocation of valuable resident work hours.